The feasibility of a patient oriented interactive panoramic virtual tour for external beam radiation therapy - Schulz, Joseph B.; Dubrowski, Piotr; Ling, Xi; Wu, Yufan; Qian, Yushen; Million, Lynn; Marquez, Carol M.; Yu, Amy (Frontiers in Oncology, 2025)
IntroductionThe integration of digital technology in healthcare, particularly for patient education and experience, is rapidly advancing. This pilot study examined the feasibility of an interactive panoramic virtual tour for improving patient experiences in an external beam radiation therapy (RT) setting at a smaller center.MethodsA virtual tour of the RT department was developed using specialized software and 360-degree 8K camera. The study utilized a two-group design: a control group (33 patients) not exposed to the tour and an experimental group (35 patients) who accessed the tour via the MyHealth platform prior to RT treatment. The survey measured levels of anxiety, comfort with treatment course, knowledge about the facility, navigation through a course of RT, and satisfaction with overall treatment on a 1–10 scale, with 10 being a more desirable outcome.ResultsThe experimental group reported improved outcomes compared to the control group across all parameters: anxiety levels were lower (mean: 7.3 ± SD: 2.6 vs. 6.5 ± 3.3; p = 0.32), though variances differed significantly (p = 0.03). Comfort levels were higher (9.1 ± 1.7 vs. 8.4 ± 2.1; p = 0.27), knowledge about the cancer center increased (8.7 ± 1.5 vs. 7.8 ± 2.4; p = 0.27) with unequal variances (p = 0.03), and ease of navigation slightly improved (9.8 ± 0.6 vs. 9.4 ± 1.9; p = 0.61). Satisfaction levels were similar in the experimental group (9.6 ± 1.1 vs. 9.5 ± 1.2; p = 0.74).ConclusionsThis pilot study provides preliminary evidence that an interactive virtual tour may enhance certain aspects of the RT patient experience, although the small sample size limits the ability to draw definitive conclusions. The integration of virtual tours into RT practices reflects a shift towards more interactive and patient-friendly approaches in healthcare by demystifying the RT process and providing accessible information. Future research with larger, more diverse cohorts at a larger institution is warranted to confirm whether these early findings generalize more broadly and to better quantify the impact of virtual tours on patient-reported outcomes.